2021
DOI: 10.1038/s41598-021-99695-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein co-expression network-based profiles revealed from laser-microdissected cancerous cells of lung squamous-cell carcinomas

Abstract: No therapeutic targets have been identified for lung squamous cell cancer (SqCC) which is the second most prevalent lung cancer because its molecular profiles remain unclear. This study aimed to unveil disease-related protein networks by proteomic and bioinformatic assessment of laser-microdissected cancerous cells from seven SqCCs compared with eight representative lung adenocarcinomas. We identified three network modules significant to lung SqCC using weighted gene co-expression network analysis. One module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Two keratins, keratin, type I cytoskeletal 2 epidermal (KRT2) and keratin, type I cytoskeletal 9 (KRT9) were down‐regulated. The observed global upregulation of keratins in this study highlights the strong keratinization process observed during LSCC, as also previously reported in laser micro‐dissected tumor cells [ 80 ]. Interestingly, keratinization might be associated with smoking, a risk factor of lung CIAC, and keratinization correlates with poor clinical outcome in LSCC [ 81 ].…”
Section: Resultssupporting
confidence: 88%
“…Two keratins, keratin, type I cytoskeletal 2 epidermal (KRT2) and keratin, type I cytoskeletal 9 (KRT9) were down‐regulated. The observed global upregulation of keratins in this study highlights the strong keratinization process observed during LSCC, as also previously reported in laser micro‐dissected tumor cells [ 80 ]. Interestingly, keratinization might be associated with smoking, a risk factor of lung CIAC, and keratinization correlates with poor clinical outcome in LSCC [ 81 ].…”
Section: Resultssupporting
confidence: 88%
“…Protein co-expression networks are emerging as a valuable tool for the study of complex phenotypes, including pathological states such as tumors [ 37 , 38 , 39 ]. Gene co-expression networks have been quite successful, providing molecular insights into tumor biology, yet for obvious reasons, these are not able to account for post-transcriptional, translational and post-translational phenomena, which may constitute important players in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to identify co-expression protein networks associated with A549/KL cells, compared with those of A549 cells, to understand how Klotho protein expression affects molecular networks associated with the malignant nature of lung carcinoma cells. Weighted gene co-expression network analysis (WGCNA), an unsupervised clustering method based on correlation network expression 14 , 15 was applied to quantitative proteome datasets. Then, Ingenuity Pathway Analysis was used to perform upstream analysis 16 of data-driven protein co-expression networks, and GeneMANIA 17 was used to identify interaction networks of proteins expressed characteristically in the A549 and A549/KL cells, respectively.…”
Section: Introductionmentioning
confidence: 99%